2021
DOI: 10.1111/jfbc.13971
|View full text |Cite
|
Sign up to set email alerts
|

A nutraceutical combination of cinnamon, purple onion, and tea linked with key enzymes on treatment of type 2 diabetes

Abstract: Background: Diabetes mellitus (DM) is concomitant with signi cant morbidity and mortality and its prevalence is accumulative worldwide. The conventional antidiabetic agents are known to mitigate the symptoms of diabetes; however, they may also cause adverse effects. This study explores the e cacy of polyherbal dietary supplement cinnamon, purple onion, and tea on the mediation of postprandial hyperglycemia for in the search of combinations with a maximal response.Materials and methods: A starch solution (3 g/k… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Currently, we have performed in silico assays to accelerate new discoveries from herbal or natural compounds and confirmed the validation of preclinical levels. These include: α-amylase and α-glucosidase activities suppressed by Garcinia linii extracts, including syringaldehyde, via docking, and further confirmed by in vitro (cell) and in vivo (diabetic mice) studies [ 289 ]; by the mixture of extracts (purple onion, cinnamon, and tea) via docking, and further confirmed by in vitro (enzyme) and in vivo (diabetic mice) studies [ 290 ]; by γ-mangostin via docking and further confirmed by in vitro (cell, enzyme) and in vivo (diabetic mice) studies [ 291 ]; by syringaldehyde via docking and further confirmed by in vitro (enzyme, organ culture) and in vivo (diabetic mice) [ 292 ] studies; and by curcumin, antroquinonol, HCD, docosanol, tetracosanol, rutin, and actinodaphnine via virtual screen and further confirmed by in vitro (cell) and in vivo (diabetic mice) studies [ 293 ]. Remarkably, drug design is a process in which new leads (efficacy drugs) are discovered which have therapeutic benefits in antidiabetic drugs and can have potential effects on the management of T2DM in human clinical trials [ 246 , 247 ].…”
Section: Perspectives Of In Silico Modelling For Discovery and Development Of Anti-diabetes Drugsmentioning
confidence: 97%
“…Currently, we have performed in silico assays to accelerate new discoveries from herbal or natural compounds and confirmed the validation of preclinical levels. These include: α-amylase and α-glucosidase activities suppressed by Garcinia linii extracts, including syringaldehyde, via docking, and further confirmed by in vitro (cell) and in vivo (diabetic mice) studies [ 289 ]; by the mixture of extracts (purple onion, cinnamon, and tea) via docking, and further confirmed by in vitro (enzyme) and in vivo (diabetic mice) studies [ 290 ]; by γ-mangostin via docking and further confirmed by in vitro (cell, enzyme) and in vivo (diabetic mice) studies [ 291 ]; by syringaldehyde via docking and further confirmed by in vitro (enzyme, organ culture) and in vivo (diabetic mice) [ 292 ] studies; and by curcumin, antroquinonol, HCD, docosanol, tetracosanol, rutin, and actinodaphnine via virtual screen and further confirmed by in vitro (cell) and in vivo (diabetic mice) studies [ 293 ]. Remarkably, drug design is a process in which new leads (efficacy drugs) are discovered which have therapeutic benefits in antidiabetic drugs and can have potential effects on the management of T2DM in human clinical trials [ 246 , 247 ].…”
Section: Perspectives Of In Silico Modelling For Discovery and Development Of Anti-diabetes Drugsmentioning
confidence: 97%
“…It was proved to be beneficial at the same time. ( Weng et al, 2021 ). The possible hypoglycemic pathway exerts its action by enhancing the activities of bioenzymes such as hexokinase and pyruvate kinase during glycolysis by increasing the content of liver glycogen and inhibit the gene expression of glucose-6-phosphatase and phosphoenolpyruvate carboxylase, which are key enzymes in the process of liver gluconeogenesis, and to maintain insulin resistance ( Prasath and Subramanian, 2011 ; Prasath et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%